Quality of Brussels sprouts (Brassica oleracea L. gemmifera DC) as affected by blanching method - Viña, Sonia Zulma (2007)
In this work, pre-blanching of Brussels sprouts was performed- using different heating media -as well as various blanching times,in order to minimize quality factors losses and browning incidence in subsequent stages of product processing and storage. Sprouts werefirstly treated for 5 min, either in water at 50 C or by microwaves, and then blanched in boiling water for 3 or 2 min, respectively. Othersamples were directly blanched by immersion in water (100 C) for 1, 3 or 4 min. Thermal history, surface colour, texture, total chlorophyll,radical scavenging activity, ascorbic acid and total flavonoids content were determined. Microwaves pre-blanching showed nodeleterious effects on total chlorophyll, radical scavenging activity, total flavonoids and ascorbic acid content of Brussels sprouts andthe moderate heat treatment induced by this method may be considered to be a useful tool to improve health properties of Brusselssprouts.